Crystallization, X-ray diffraction analysis and preliminary structure determination of the polygalacturonase PehA from Agrobacterium vitis - Vordtriede, Paul B. (International Union of Crystallography, 2008)

(untitled)
Polygalacturonases are pectate-degrading enzymes that belong to glycoside hydrolase family 28 and hydrolyze the α-1,4 glycosidic bond between neighboring galacturonasyl residues of the homogalacturonan substrate. The acidic polygalacturonase PehA from Agrobacterium vitis was overexpressed in Escherichia coli, where it accumulated in the periplasmic fraction. It was purified to homogeneity via a two-step chromatography procedure and crystallized using the hanging-drop vapour-diffusion technique. PehA crystals belonged to space group P2(1), with unit-cell parameters a = 52.387, b = 62.738, c = 149.165 Å, β = 89.98°. Crystals diffracted to 1.59 Å resolution and contained two molecules per asymmetric unit. An initial structure determination by molecular replacement indicated a right-handed parallel β-helix fold.